The immunosuppressive potential of human amniotic membrane extract - Duque, Marta (2018)
Both mesenchymal stromal cells (MSCs) and human amniotic membrane (hAM) possess immunoregulatory potential, driving several studies to focus on their application in the prevention and treatment of immunological disorders, and especially on their ability to modulate T cell responses. However there is little information regarding the concrete effects over different activation and differentiation stages of T cells. The main objective of this study was to determine whether or not a hAM extract (hAME) had a differential effect over different T cell subpopulations (CD4+ and CD8+ T naïve, central memory, effector memory and effector cells). Thus, peripheral blood mononuclear cells (PBMC) were cultured in the presence or absence of hAME and stimulated with phorbol myristate acetate (PMA) plus ionomycin. Cell proliferation was evaluated through a thymidine incorporation assay and the percentages of pro-inflammatory cytokine producing T cells were determined by flow cytometry. The phenotype of hAM-derived cells was also assessed by flow cytometry. Plus, the mRNA expression of selected genes was evaluated in purified CD4+ and CD8+ T cells, regulatory T cells (Treg) and γδ T cells. The hAM-derived cells contained hAM epithelial cells and MSCs. The extract displayed an antiproliferative effect and reduced the frequency of tumor necrosis factor-alpha (TNFα), interferon gamma (IFNγ), and interleukin-2 (IL-2) producing cells, within all T cell subsets. The hAME also diminished the frequency of IL-17 and IL-9 producing T cells. The pattern of inhibition varied between CD4+ and CD8+ T cells, between T cell subsets, and depending on the cytokine under study. The hAME also produced a decrease in mRNA expression of granzime B, perforin and activating receptor NKG2D by CD8+ T cells, γδ T cells as well as an upregulation of Foxp3 and IL-10 gene expression in CD4+ T cells and an upregulation of IL-10 mRNA expression in Treg cells. These results show that the hAME differentially regulates different T cell subsets and therefore the effect of the hAME over T cells responses will depend on the T cell subpopulations involved. Still, the hAME has an overall antiinflammatory action.